Research on the mechanism of gel accelerator on gel transition of PAN solution by rheology and dynamic light scattering - Guo Zhaoyu (De Gruyter, 2020)
The rheological properties of PAN/DMSO solution and the size and distribution of PAN coils were studied by rheology and dynamic light scattering (DLS) measurements. It was found that water could be used as a gel accelerator and increase the gel transition temperature T gel and the storage modulus G′ as well as decrease the damping factor tan δ through rheological measurements. DLS test shows that the average size of PAN coils increases significantly with the increase in gel accelerator content. In addition, the gel accelerator can change the mobility of PAN chains during the cooling process. The results show that the gel accelerator can enhance the entanglement of PAN macromolecular chains and improve the formation of three-dimensional network gel structure, so that PAN solution is more prone to gel transition during the cooling process.